Sustainable enterprise capital management - Dariusz Klimek (Economies, 2020)
The paper presents the idea of a new method of sustainable enterprise capital management. The idea is based on a principle that states that the faster an enterprise achieves and maintains a balance between its capitals, the more effective the management is. The concept forms a part of the search for an alternative to net profit, which is a basic but outdated measure in modern times. After the introduction, the author outlines the basic principles and foundations of the new method. After introducing the principles and assumptions of the new idea, the author, in his paper, describes the studies that aimed at a practical checking of the possibilities of measuring the effectiveness of the company's economic condition and the effects of management in accordance with the new principles. They were carried out in one of the food industry companies, whose shares are listed on the Warsaw Stock Exchange. Two new economic indicators were used in the study. The general conclusion of the study is as follows: new principles of sustainable capital management can be applied in practice to measure the effectiveness of the enterprise and the work of the management board, but there are still many conditions and problems listed in the paper that should be the subject of further work. The issue that still needs a lot of research within the whole idea is the problem of valuing the current and optimal level of corporate capital. The conclusions outline the strengths and weaknesses of the new method.
Keywords: 330; enterprise capital; enterprise resources; management efficiency; sustainable management